2022
DOI: 10.3390/antiox11081457
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptome Analysis of Radiation Pneumonitis Mice

Abstract: Radiation-induced lung injury (RILI), especially radiation pneumonitis (RP), is a common clinical complication associated with thoracic radiotherapy for malignant tumors. However, the specific contributions of each cell subtype to this process are unknown. Here, we provide the single-cell pathology landscape of the RP in a mouse model by unbiased single-cell RNA-seq (scRNA-seq). We found a decline of type 2 alveolar cells in the RP lung tissue, with an expansion of macrophages, especially the Fabp4low and Spp1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…4g). Downregulation of the Hbb-bt and Hba-at genes may involve the evasion of ROS-mediated antioxidants in NK cells [52,53]. To further con rm this nding, we identi ed that the activation of BCl2 (anti-apoptotic protein) (Fig.…”
Section: Nk Cell Subsets Induced Pro-in Ammatory Response After Treat...mentioning
confidence: 80%
“…4g). Downregulation of the Hbb-bt and Hba-at genes may involve the evasion of ROS-mediated antioxidants in NK cells [52,53]. To further con rm this nding, we identi ed that the activation of BCl2 (anti-apoptotic protein) (Fig.…”
Section: Nk Cell Subsets Induced Pro-in Ammatory Response After Treat...mentioning
confidence: 80%
“…MHC-I expression on the surface of the tumor cells and the ability of dendritic cells (DCs) to present antigens can be increased after radiation. Miaomiao Yang et al proposed that RP tissue had less naive CD8 + T cells, more effector T cells, and a more diverse B cell subtype [35]. Based on available evidence, radiation-induced RP can activate the immune response to some extent, which could be bene cial for the survival of lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the cGAS/STING pathway is enriched in radiation-induced fibrosis [ 142 ]. Furthermore, the role of the STING pathway in liver, kidney and lung fibrosis has also been demonstrated [ 143 145 ].…”
Section: Mechanisms Of Radiation-induced Fibrosismentioning
confidence: 99%